School teenager knowledge on contraceptive methods - Mariane Cristina Carlucci Molina; Patrica Grazieli Silverio Stoppiglia; Christine Baccarat de Godoy Martins; Lidiane Cristina da Silva Alencastro (O Mundo da Saúde)
Currently, issues relating to contraception in adolescence become relevant, particularly as regards knowledge of adoles- cents about their use. The study aimed evaluation of the knowledge on contraceptive methods and their utilization among adolescents of the secondary grade of public schools in Cuiaba-MT. Quantitative transversal study, conducted in the months of November to December 2013, with 691 teenagers. They were interviewed with closed questions / multiple choice questionnaires. Data were analyzed with Epi Info 3.5.2 statistics software. The major age for sexual initiation was 15 years. About 1.44% of the teenagers interviewed have 1 or more children. Men make use principally of male condoms (52.8%), while women usually combine more than 1 method (14.9%). The commonest errors on answering how to use contraceptive methods were related to: male condoms (30.7%), female condoms (25.4%), hormonal pills (30.7%), morning-after pills (28.8%), coitus interruptus (41%) and calendar-based abstinence (33.8%). Results call attention to the high importance of public health efforts targeted to the adolescents and the insertion of health services in the school/social environments.